The unusual co-assembly of H- and M-chains in the ferritin molecule from the Antarctic teleosts Trematomus bernacchii and Trematomus newnesi - GIORGI, ALESSANDRA; MIGNOGNA, Giuseppina; GATTONI, Maurizio; CHIARALUCE, Roberta; CONSALVI, Valerio; CHIANCONE, Emilia; STEFANINI, Simonetta; Giuliano Bellapadrona (Archives of Biochemistry and Biophysics, 2008)
Ferritins from the liver and spleen of the cold-adapted Antarctic teleosts Trematomus bernacchii and Trematomus newnesi have been isolated and characterized. Interestingly, only H- and M-chains are expressed and no L-chains. The H-chains contain the conserved ferroxidase center residues while M-chains harbor both the ferroxidase center and the micelle nucleation site ligands. Ferritins have an organ-specific subunit composition, they are: M homopolymers in spleen and H/M heteropolymers in liver. The M-chain homopolymer mineralizes iron at higher rate with respect to the H/M heteropolymer, which however is endowed with a lower activation energy for the iron incorporation process, indicative of a higher local flexibility. These findings and available literature data on ferritin expression in fish point to the role of tissue-specific expression of different chains in modulating the iron oxidation/mineralization process. © 2008 Elsevier Inc. All rights reserved.